Pediatric scrub typhus complicated by cytokine storm, hyperferritinemia, and cerebral infarcts: A case report - Ajay Gupta; Vidya B Ghosh; Anil K Singh (Journal of Pediatric Critical Care, 2022)
Hyperferritinemia has been associated with increased mortality in severe sepsis and also described with scrub typhus. We describe a case of a 10-year-old child with acute febrile illness, altered sensorium, seizures, and left hemiparesis, along with septic shock. The child had markedly elevated inflammatory markers, along with hyperferritinemia and increased D-dimer. Serological tests for scrub typhus were positive. The child was started on doxycycline along with supportive management. In view of hyperferritinemic sepsis with accompanying cytokine storm, septic shock, and disseminated intravascular coagulopathy, IgM-enriched intravenous immunoglobulin and dexamethasone were administered with good outcome. Neuroimaging revealed cerebral infarcts managed with low-molecular-weight heparin and aspirin. The child was discharged with normal sensorium and with improving left hemiparesis. Early use of immunomodulatory drugs in such atypical presentations in scrub typhus may reduce mortality, and further research is warranted.